Health and productivity of East African Zebu under village management in a tsetse area on the coast of Kenya - Maloo, S.H.; Chema, S.; Koskey, J.; Kimotho, P.; Trail, J.C.M.; Murray, M. (OAU/STRC, 1985)
Evaluates the health and productivity of East African Zebu cattle under village management in a tse-tse infested area surrounding the Muhaka Forest on the Kenya Coast south of Mombassa, and assesses the cost-effectiveness of intervention with trypanocidal drugs.